Healthcare innovation in Greece: The views of private health entrepreneurs on implementing innovative plans - Sotiris Apostolopoulos; Ilias Makris; Stavros Stavroyiannis (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
In the field of healthcare innovation, Greece ranks 26th in FREOPP's World Index of Healthcare Innovation (WIHI) 2021 analysis. Such a standing illustrates low performance in the dimensions of quality, science and technology and fiscal sustainability. This article seeks to shed light on this backwardness and examine the obstacles and weaknesses in the development of innovative projects by Greek health entrepreneurs. Furthermore, this research aims to trace entrepreneurs' views on innovation issues and assess the existence of innovative plans from four perspectives: at the level of service to citizens, in the functionality of health business structures, at the level of facilities and technology, and in a clinical setting. Qualitative research was conducted with the entrepreneurs of 12 health companies in the form of semi-structured interviews. This study has shown that healthcare entrepreneurs do not reject the development of innovative projects and that those who have implemented innovative practices have had positive results; however, various obstacles negatively impact the implementation of innovative ideas. A primary research contribution will capture the factors that negatively affect the development of innovative projects and represent a crucial element for Greece to remove barriers and improve its performance on innovation issues. The results of the research will provide support for not only innovation decision-making centres but also other health entrepreneurs.
Keywords: 650; health enterprises; innovation; innovative ideas; innovative projects